Enhancing the Thai Film Industry Through Virtual Learning: A Sustainable Approach to Language Skill Development and Soft Power Expansion - Piayura, Orathai; Boonmas, Thidarat; Wongphongkham, Niyom; Sae-joo, Phongthanat; Narongchai, Wanichcha; Wongphongkham, Hava; Promphakping, Buapun (Journal of Ecohumanism, 2024)
In an era of globalization, countries and people are progressively interconnected with soft power playing a crucial role in expanding influence through collaboration and cultural exchange. The Thai film industry, despite its global recognition, encounters challenge due to limited English language proficiency among its professionals, which hampers its potential for international engagement and actions. This study intends a virtual learning model designed to enhance language skills and support the growth of soft power within the Thai film industry. Employing technologies such as the Metaverse, the model integrates learning across all stages of film production—pre-production, production, and post-production. Lining up with SDG 4 and national policies, the study adopts an action research approach to gauge the impact of this model on industry professionals. Ultimately, this research aims to provide a sustainable framework for developing language skills and flourishing Thailand’s soft power, driving the future growth of the Thai film industry on the macro stage.